2016
DOI: 10.1292/jvms.16-0198
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of tea catechin against canine oral bacteria and the functional mechanisms

Abstract: Epigallocatechin gallate (EGCG) is the major polyphenolic compound of green tea. Polyphenolic compounds were extracted from the leaf of Camellia sinensis (Japanese green tea), and the minimum inhibitory concentration against canine oral bacteria was measured. Subsequently, we investigated the inhibitory effects of polyphenolic compounds and EGCG on the growth of canine oral bacteria. EGCG showed antimicrobial activity against a model bacterium, Streptococcus mutans. Our results indicate that EGCG can inhibit t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 32 publications
1
25
0
2
Order By: Relevance
“…A formal investigation by Tohoku University has concluded that the data reported in this article are the sole property of Tohoku University and have been reported in Bai et al [2]. All authors agree with this retraction.…”
Section: Retractionsupporting
confidence: 70%
“…A formal investigation by Tohoku University has concluded that the data reported in this article are the sole property of Tohoku University and have been reported in Bai et al [2]. All authors agree with this retraction.…”
Section: Retractionsupporting
confidence: 70%
“…Moreover, the colony forming unit (CFU) of S. mutans obtained from biofilm formed in the presence of EGCG were less than that formed in the control culture. These indicate that EGCG had an inhibitory effect on biofilm formation [12]. It has been reported that in addition to binding to lipid layers and peptidoglycan, EGCG interferes with extracellular polymeric material so-called glycocalyx.…”
Section: Anti-biofilm Effectsmentioning
confidence: 86%
“…EGCG at the concentrations between 78 and 625μg/mL inhibited multi-drug resistant Acinetobacter baumannii [11]. Various bacteria isolated from canine oral cavity were sensitive to the polyphenolic compounds mix and EGCG [12]. Minimum inhibitory concentration (MIC) ranges were 0.1-0.8mg/mL for poly-phenolic compounds and 0.0125-0.1mg/mL for EGCG.…”
Section: Green Tea Compositionmentioning
confidence: 99%
“…It causes demineralization of inorganic tooth structure by metabolizing sucrose to lactic acid. It can also colonize tooth surfaces and initiate plaque formation through their ability to synthesize and bind extracellular polysaccharides (glucan) using the enzyme glucosyltransferase (Bai et al, 2016;Lalwani et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Attention was driven to the use of natural plant extracts for their health care needs as they are effective, nontoxic, and economical and usually have no side effects. Green tea and pomegranate are among these plants (Bai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%